Quantitative Ubiquitylomic Analysis of the Dynamic Changes and Extensive Modulation of Ubiquitylation in Papaya During the Fruit Ripening Process - Mo, Yuxing; Jiang, Bian; Huo, Jingxin; Lu, Jiayi; Zeng, Xiaoyue; Zhou, Yan; Zhang, Tao; Yang, Min; Wei, Yuerong; Liu, Kaidong (Frontiers in Plant Science, 2022)
Lysine ubiquitination is a highly conserved post-translational modification with diverse biological functions. However, there is little available information on lysine ubiquitination of non-histone proteins in papaya (Carica papaya L.). In total, 3,090 ubiquitination sites on 1,249 proteins with diverse localizations and functions were identified. Five conserved ubiquitinated K motifs were identified. Enrichment analysis showed that many Hsps were differentially ubiquitinated proteins (DUPs), suggesting an essential role of ubiquitination in degradation of molecular chaperone. Furthermore, 12 sugar metabolism-related enzymes were identified as DUPs, including an involvement of ubiquitination in nutrimental changes during the papaya ripening process. The ubiquitination levels of five fruit ripening-related DUPs, including one ethylene-inducible protein, two 1-aminocyclopropane-1-carboxylic acid oxidases, one endochitinase, and one cell wall invertase, were significantly changed during the ripening process. Our study extends the understanding of diverse functions for lysine ubiquitination in regulation of the papaya fruit ripening process.